Comparative Analysis of Transcriptome Responses to Cold Stress in Galeruca daurica (Coleoptera: Chrysomelidae). Issue 6 (21st November 2019) - Zhou, Xiao-Rong; Shan, Yan-Min; Tan, Yao; Zhang, Zhuo-Ran; Pang, Bao-Ping
Abstract: Galeruca daurica (Joannis) has become a new insect pest in the Inner Mongolia grasslands since 2009, and its larvae and eggs have strong cold tolerance. To get a deeper insight into its molecular mechanisms of cold stress responses, we performed de novo transcriptome assembly for G. daurica by RNA-Seq and compared the transcriptomes of its larvae exposed to five different temperature treatments (−10, −5, 0, 5, and 25°C for 1 h and then recovered at 25°C for 1 h), respectively. Compared with the control (25°C), the numbers of differentially expressed genes (DEGs) decreased from 1, 821 to 882, with the temperature declining from 5 to −10°C. Moreover, we obtained 323 coregulated DEGs under different low temperatures. Under four low temperatures (−10, −5, 0, and 5°C), a large number of genes were commonly upregulated during recovery from cold stresses, including those related to cuticle protein, followed by cytochrome P450, clock protein, fatty acid synthase, and fatty acyl-CoA reductase; meanwhile, lots of genes encoding cuticle protein, RNA replication protein, RNA-directed DNA polymerase, and glucose dehydrogenase were commonly downregulated. Our findings provide important clues for further investigations of key genes and molecular mechanisms involved in the adaptation of G. daurica to harsh environments.